Ultrastructural localisation of nitric oxide synthase, endothelin and binding sites of lectin (from Bandeirea simplicifolia) in the rat carotid artery after balloon catheter injury - LOESCH, A. (1997)

(untitled)
An immunocytochemical and cytochemical study has been made on the ultrastructural localisation of type III (endothelial) nitric oxide synthase, endothelin-1 and the binding sites of lectin from Bandeirea simplicifolia to the endothelium surface-associated glycoproteins in the rat left common carotid artery at 1 and 28 d after Fogarty embolectomy balloon catheter-induced injury. Controls were carotid arteries from sham operated rats. In the controls, the immunoreactivity to nitric oxide synthase-III and endothelin-1 was localised in different proportions in vascular endothelial cells (36·9%±4·3 and 7·6%±2·7, respectively); immunoreactivity was confined to the cytoplasm and the membranes of intracellular organelles and structures. In contrast, staining with lectin was localised on the luminal surface of all endothelial cells. 1 d after injury, platelets were adherent to the endothelium-denuded intima. Some of the platelets displayed immunoreactivity to nitric oxide synthase-III and endothelin-1 and were stained with lectin. 28 d after injury, a neointimal thickening of substantial size was present. Subpopulations of the regrown endothelial cells covering the luminal surface of the neointima showed positive immunoreactivity to nitric oxide synthase-III and endothelin-1 but there was a significant decrease in the proportion of nitric oxide synthase-III-containing endothelial cells (17·2%±1·9; P < 0·001) and a significant increase in the proportion of endothelin-1-containing endothelial cells (36·9%±4·7; P < 0·001) compared with the controls. Staining with lectin was associated with the cell membrane of all endothelial cells and in addition with cells located ‘deeper’ in the neointima which showed lectin-positive plasmalemma, Golgi complex and multivesicular bodies/lysosomes. In conclusion, regenerated endothelial cells of the neointima showed reduced population (2–fold) of nitric oxide synthase-III- and increased population (5–fold) endothelin-1-positive cells. The subendothelial location of some lectin-stained cells after balloon catheter injury indicates the heterogeneity of the neointima and suggests that some of these cells are involved in early angiogenesis. 24 h and 28 d after injury some platelets showed positive immunoreactivity for nitric oxide synthase-III and endothelin-1.